Ferulic Acid Attenuates Hypoxia/Reoxygenation Injury by Suppressing Mitophagy Through the PINK1/Parkin Signaling Pathway in H9c2 Cells - Luo, Chenxi; Zhang, Yehao; Guo, Hao; Han, Xiao; Ren, Junguo; Liu, Jianxun (Frontiers in Pharmacology, 2020)
Ferulic acid protects against cardiac injury by scavenging free radicals. However, the role of mitophagy in ferulic acid-induced cardioprotection remains obscure. In the present study, H9c2 cells were exposed to hypoxia/reoxygenation and ferulic acid treatment during hypoxia. We illustrated the impact of ferulic acid on oxidative damage in H9c2 cells. Our results showed that ferulic acid significantly reversed apoptosis induced by hypoxia/reoxygenation injury and reduced mitochondrial dysfunction, evidenced by a decline in the overproduction of reactive oxygen species and ATP depletion, and recovery of the membrane potential. We also found that mitophagy, a selective form of autophagy, was excessively activated in H9c2 cells subjected to hypoxia/reoxygenation. Ferulic acid reduced the binding of mitochondria to lysosomes, down-regulated the PINK1/Parkin pathway, and was accompanied by increased p62 and decreased LC3-II/LC3-I levels. Ferulic acid also antagonistically reduced the activation of mitophagy by rapamycin. These findings suggest that ferulic acid may protect H9c2 cells against ischemia/reperfusion injury by suppressing PINK1/Parkin-dependent mitophagy. Accordingly, our findings may provides a potential target and powerful reference for Ferulic acid in clinical prevention and treatment of hypoxia/reoxygenation injury.